Reimagining Grassroots Women’s Leadership: Epistemic Agency and Collective Power in Rural Indonesia - Titiek Kartika Hendrastiti (Goodwood Publishing, 2026)
Purpose: This study aims to explore grassroots women’s leadership as a collective and epistemic process rooted in everyday struggles for justice, care, and survival, focusing on women in rural Indonesia. Research Methodology: This study utilizes participatory methods and feminist-decolonial analysis, drawing on field experiences and reflections from Her Place, Her Power: Growing Together for Women’s Rights and Agency in Rural Communities. The study examines the leadership of women in rural Indonesian contexts, such as forest-edge, agrarian, and coastal areas. Results: The findings reveal that rural women develop leadership not as positional authority but as epistemic agency, creating and sharing knowledge based on lived experiences. They challenge exclusionary governance, negotiate recognition, and co-create strategies for gender equality and environmental well-being. Conclusions: This study concludes that these women’s leadership is relational and transformative, rooted in care ethics, intergenerational solidarity, and community-based learning. Epistemic leadership provides a path toward gender-just and inclusive innovation, suggesting a need to rethink leadership development and knowledge systems. Limitations: This study is limited to rural Indonesia and may not fully represent the experiences of women in other contexts. Contributions: This study contributes to the fields of gender studies, rural development, and leadership by offering a new perspective on leadership that values local women as co-producers of transformative change. It provides insights for policymakers, community leaders, and scholars focused on gender equality and sustainable development.